(untitled) (Global Journal of Human-Social Science, 2025)
Over the more than 50 years of diplomatic relations between Brazil and China various political economic cultural and educational initiatives have been strengthened as part of South-South cooperation Among the institutional partnerships between the two countries exchanges of experiences in teaching research and university management have brought the academic communities of the University of Pernambuco UPE and the Central University of Finance and Economics CUFE closer together This collaboration has materialized in projects such as the Confucius Institute and the organization of thematic seminars for sharing educational ideas among the academic communities of these institutions Using a qualitative approach we analyzed the outcomes of the seminars hosted by UPE and CUFE alongside the enhancement of educational digitalization From our analysis we observed that the use of educational methodologies and information technologies such as distance learning and artificial intelligence played a crucial role in addressing demands across various socio-cultural sectors in both countries